Education en valores y ciencias sociales - Andrés Palma Valenzuela (Firenze University Press, 2017)
In order to enrich the debate about teachers' formation, there is a need to improve the education in values (EiV) from the perspective of a Social Sciences' didactic (SSCI), exploring for this purpose its mutual implications. Being aware of the difficulties that may arise from the concept of value and its inclusion in the syllabus, we assume such challenge in order to achieve, as a response to these deficiencies, five goals: rediscovering the curricular contents in the process of teaching SSCI as an area of attitudinal learning that includes the EiV; valuing the difficulty of defining and pinpointing values in the syllabus; discovering the EiV as a requirement in this area; outlining proposals for attitudes and competencies in EiV that can be assumed in the didactic process and establishing a direct connection between contents and activities of EiV within the frame of SSCI.